Requirements of Escherichia coli to survive stress induced by the secretin, pIV : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University, Manawatū, New Zealand - Bagley, Stefanie Jayne (Massey University, 2018)
Pathogenic Gram-negative bacteria utilise complex multiprotein and functionally unrelated trans-envelope machineries to secrete toxins and other virulence factors. Such machineries are referred to as secretion systems. These contain large, membrane-inserted homologous channels called a secretin. These secretion systems include the type II and III secretion systems (T2SS and T3SS), type IV pili assembly system (T4PS), and the filamentous phage assembly-secretion system (FFSS). Secretins are homomultimers with radial symmetry blocked by an inner gate or septum and have a pore size of up to 10 nm. As determined by previous studies on the FFSS secretin, pIV, and the T3SS secretin, InvG, there is a cost associated with the insertion of large membrane channels. Membrane integrity is disrupted, leaving the bacterial cell highly susceptible to antibiotics and environmental stressors. As a result, Gram-negative bacteria have developed stress response pathways which upregulate genes to mitigate this secretin induced stress. These are the Phage Shock Protein response (Psp), Conjugative plasmid expression (Cpx), Regulation of capsular synthesis (Rcs), and SoxRS Superoxide response (Sox). Not all individual genes within these stress response pathways are necessarily required for the survival of Escherichia coli expressing secretin. Stress can be induced in E. coli by expression of leaky pIV mutants as they are open, not gated, under physiological conditions and imitate the actively secreting channel. A synthetic lethality assay was performed to determine the importance of the key regulators from four stress response pathways (PspF, CpxR, RcsA, RcsB, SoxR, and SoxS) on cell viability in the presence of the leaky secretin mutant, pIV-E292K. Here it was determined that the Psp, Rcs and, (to a lesser extent), Cpx regulons, confer a protective effect on E. coli K-12 experiencing stress induced by pIV-E292K. Expression of pIV-E292K mutant also induced an Rcs-dependent capsular polysaccharide phenotype indicating upregulation of Rcs in response to leaky pIV production. These three responses are potential drug targets in the fight against antibiotic-resistant infections. Inhibition of the stress response may prevent mitigation of membrane stress, thereby killing the channel-expressing bacteria.
Figures used with permission.
Keywords: Escherichia coli; Gram-negative bacteria; Secretin; Stress (Physiology); Cell membranes; Drug resistance in microorganisms